Information technologies, social change and the future : online journalism in Portugal - Sousa, Helena (2006)
The main objective of this article is to equate social change and new information and communication technologies (ICTs). From a multitude of theoretical entry points, the author decided to outline the key concept of time and to discuss its explanatory possibilities in a specific context: the development of online journalism in Portugal over the last decade. She takes the view that general formulations about the relationship between social change and technology could not elucidate the nature of social transformations nor the driving and opposing forces in particular contexts. Technology per se is not a relevant explicative variable but, in context, it certainly contributes to clarify social change. This article argues that the understanding of different simultaneous rhythms of change requires complementary incursions through the past, the present and the empirically accessible future.